Technical and environmental issues at pre- feasibility level for sustainable organic production of guapote (Parachromis managuensis and P. dovii) and freshwater clam (Myce - topodidae) in Jiménez-Pococí, Limón , Costa Rica - Castro Méndez, Adolfo (2018)
This study for the development of a new sustainable organic aquaculture company with new non-traditional products, is created to help the Pococí location development, and try to reduce the impacts exerted several problems in this area and throughout the country.  Among the problems that aims to address are food shortages quality, poor management in aquaculture, looking for savings and recycling of water resources and counteract excessive current marine exploitation, reforestation with endemic and / or endangered species and reintroduction endangered species of animals (mainly water) and directly contribute to the rescue of elderly in conditions of neglect of the area by supporting the Angel of Love Foundation, which performs this management in the canton.  The document generally made a detailed study of prefeasibility and viability, developing a market analysis for the area and a major customer that operates throughout the country (Corporation Automercado S.A) as well as an analysis and technical, administrative studies and organizational, legal and main attributes, environmental, social, economic and financial studies. All derived from the company creation to evaluate and understand the effects of the future organization.  The main results are that an unsatisfied demand due to the picture presented by the products will, as a large acceptance and high demands determined, which technically allows supply to part of the market investigation.  Environmentally the company covers all requirements and regulations related to the activity, and rather contributes to the improvement and environmental development, wildlife through activities, mainly only use rainwater for production, coupled with the use of high technology, biotechnology as EM (effective microorganisms among other factors), implementation of HACCP (hazardous activities and critical control points for its acronym in English), Organic Management Plan, GAP (good aquaculture practices), among other steps of quality and international safety. In addition to being a company based on codes of ethics, CSR (corporate social responsibility), continuous improvement and seek improvement and growth of employees.  For this article, we will focus only on the technical and environmental study, analysis linked strictly and directly related to the project. The market issues are done.